2013
DOI: 10.1155/2013/563919
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Plasma Obestatin and Early Arteriosclerosis in Patients with Type 2 Diabetes Mellitus

Abstract: We investigated the correlation between obestatin and metabolic parameters and carotid intima-media thickness (IMT) in plasma of patients with type 2 diabetes mellitus (T2DM). We collected 103 patients aged from 60 to 83 years (69.26 ± 5.83 years) form January, 2007 to May, 2009. All patients were divided into normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and T2DM according to the oral glucose tolerance test (OGTT). We found that higher levels of fasting insulin (Fins), fasting blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(34 reference statements)
1
12
0
2
Order By: Relevance
“…Estimation of serum level of NO through the Double Antibody Sandwich Technique [25]. Estimation of MMP-9 protein expression in Aorta and tibia tissue samples using enzymelinked immunosorbent assay kits (Elabscience Biotechnology Co Ltd, Beijing, China) according to the manufacturer's instructions.…”
Section: Concise Methodologymentioning
confidence: 99%
“…Estimation of serum level of NO through the Double Antibody Sandwich Technique [25]. Estimation of MMP-9 protein expression in Aorta and tibia tissue samples using enzymelinked immunosorbent assay kits (Elabscience Biotechnology Co Ltd, Beijing, China) according to the manufacturer's instructions.…”
Section: Concise Methodologymentioning
confidence: 99%
“…Similar to the physiological situation, the data have been somewhat inconsistent (likely due to the reasons previously discussed), although it seems that obestatin levels are generally altered in diabetes and obesity. For example, decreased circulating obestatin has been documented in overweight/obese patients and those with impaired glucose control, metabolic syndrome, T2DM and insulin resistance (Anderwald‐Stadler et al ., ; Qi et al ., ; Fontenot et al ., ; Guo et al ., ; Gao et al ., ; Huda et al ., ; Nakahara et al ., ; Zou et al ., ; Beasley et al ., ; Cui et al ., ; Shen et al ., ; Gu et al ., ; Wang et al ., ). Inverse correlations between circulating obestatin and body mass index, insulin, glucose, leptin, homeostatic model assessment of insulin resistance and glycated haemoglobin have also been reported (Lippl et al ., ; Nakahara et al ., ; Gu et al ., ; Shen et al ., ; Wang et al ., ), with reduced numbers of obestatin‐positive cells evident in the gastric mucosa of overweight/obese subjects with abdominal obesity (Gao et al ., ).…”
Section: Metabolic Actions Of Obestatinmentioning
confidence: 99%
“…Previous studies have shown that the effects of obestatin on appetite, food intake and gastric secretions is opposite to ghrelin [ 21 , 22 ]. Obestatin has been identified as a hormone associated with insulin resistance that suppresses food reabsorption, inhibits gastric emptying and decreases weight gain [ 23 , 24 ]. However, the true role of obestatin in the mechanism of obesity has not been fully determined yet; in some animal studies, it was found that obestatin unlike ghrelin may provide a new target for the control of obesity [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%